Diverse voices in modern US moral theology - Curran, Charles E. (Moral traditions series., 2018)
In Curran's latest book, Diverse Voices in Modern US Moral Theology, he presents the twelve leading voices of Catholic Moral Theology (CMT) from the early twentieth century to the present. (One could argue that Curran, himself, should be in this book.) The book discusses key individuals, and one movement that included multiple people, in the development of the field to show how it has evolved. The New Wine, New Wineskins movement was included because the movement was led by lay people, showing how dramatically the face of CMT changed. The book provides overviews of the major figures in CMT without offering critique in order to foster a dialogue between liberal and conservative approaches to MT, and demonstrates that one's approach to CMT is very rooted in one's historical circumstances--called Sitz-im-Leben in the field. It is the last aim that provides the main argument for the book; that CMT has changed and each of these theologians have shifted thinking largely because of the historical context in which they wrote. Curran also shows that those on opposing sides of the debates in moral theology have become more divided and urges in his conclusion that they have more conversations with each other and not just discussions within each side.